THE IMPACT OF DEBATE HABIT TOWARD SPEAKING SKILL AT ENGLISH EDUCATION DEPARTMENT UNIVERSITAS MUHAMMADIYAH YOGYAKARTA - Sofi Nurani (PBI 15 UMY 048, 2015)
*48 There are many students in English Education Department of Universitas Muhammadiyah Yogyakarta (EED UMY) had less ability in speaking, including lack of confidence, fluency, and speaking aspects. Based on researcher’s experience, debate activity could improve speaking skill since the activity in debate was about rising argument, idea and rehearsing speaking skill. This study investigated students’ speaking skill. Also, this study was aimed at finding out the debate habit at EED UMY and its impact toward students’ speaking skill. The researcher distributed questionnaires to 31 samples. The samples were students of EED UMY who join debate activity. The findings showed that debate activity in EED UMY was very good, it is included their frequency in debate activity. Finally, this research revealed that the contribution impact of debate habit toward speaking skill was 24.7%. In conclusion, there was significant and positive impact of debate habit toward speaking skill at English Education Department Universitas Muhammadiyah Yogyakarta.